Henri Bosmans S.J. (1852–1928) – grondlegger van de geschiedenis van de wiskunde in België - Heeffer, Albrecht (Studium, 2013)
Henri Bosmans S.J. (1852–1928) – grondlegger van de geschiedenis van de wiskunde in België